A legal review on the classification of official secrets under the Official Secrets Act 1972 / Amirul Ezuan Azizul Karim - Azizul Karim, Amirul Ezuan; Mohd Zamani, Harshaan; Ismail, Mohd Arif; Mohd Saifiizzaman, Muhammad Shakeel (Faculty of Law, 2013)
This project paper is concerned on the official secrets particularly classification of official secrets under the Official Secrets Act 1972. Basically, section 2(1) of the Official Secrets Act 1972 provides the definition of official secrets in which it includes scheduled official secrets and classified official secrets. However, this definition is too broad as there is no clear definition of classified official secrets. Further, it is unclear as to what types of documents that fall under the category of information that may be classified as secret. The scope of this project paper analyses the comprehensiveness and effectiveness of laws with regard to classification of information in Malaysia, India and United States of America. Besides, this project paper compares the development of laws with respect to classification of information that took place effectively in India and United States of America. As a result, certain recommendations are proposed to review and amend the current law in regard to classified official secrets which is provided under the Official Secrets Act 1972.